Targeted volatolomics of human monocytes: Comparison of 2D-GC/TOF-MS and 1D-GC/Orbitrap-MS methods - Zemánková, Kristýna; Pavelicová, Kristýna; Pompeiano, Antonio; Mravcová, Ludmila; Černý, Martin; Bendíčková, Kamila; Hortová Kohoutková, Marcela; Dryahina, Kseniya; Vaculovičová, Markéta; Frič, Jan; Vaníčková, Lucie (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2021)
Blood is a complex biological matrix providing valuable information on nutritional, metabolic, and immune status. The detection of blood biomarkers requires sensitive analytical methods because analytes are at very low concentrations. Peripheral blood monocytes play a crucial role in inflammatory processes, and the metabolites released by monocytes during these processes might serve as important signalling molecules and biomarkers of particular physiological states. Headspace solid-phase microextraction (HS-SPME) combined with two different mass spectrometric platforms, two-dimensional (2D) gas chromatography coupled to time-of-flight mass spectrometry (2D-GC/TOF-MS) and one-dimensional gas chromatography coupled to Orbitrap mass spectrometry (GC/Orbitrap-MS), were applied for the investigation of volatile organic compounds (VOCs) produced by human peripheral blood monocytes. An optimized method was subsequently applied for the characterization of changes in VOCs induced by lipopolysaccharides (LPS) and zymosan (ZYM) stimulation. Overall, the 2D-GC/TOF-MS and the 1D-GC/Orbitrap-MS analyses each yielded about 4000 and 400 peaks per sample, respectively. In total, 91 VOCs belonging to eight different chemical classes were identified. The samples were collected in two fractions, conditioned media for monitoring extracellularly secreted molecules and cell pellet samples to determine the intracellular composition of VOCs. Alcohols, ketones, and hydrocarbons were the main chemical classes of the metabolic profile identified in cell fractions. Aldehydes, acids and cyclic compounds were characteristic of the conditioned media fraction. Here we demonstrate that HS-SPME-2D-GC/TOF-MS is more suitable for the identification of specific VOC profiles produced by human monocytes than 1D-GC/Orbitrap-MS. We define the signature of VOCs occurring early after monocyte activation and characterise the signalling compounds released by immune cells into media.
Keywords: Biomarker; Reproducibility of Results; Gas Chromatography-Mass Spectrometry; GCxGC-TOF-MS; lidé; reprodukovatelnost výsledků; Volatile organic compounds; Monocytes; těkavé organické sloučeniny; Solid Phase Microextraction; monocyty; mikroextrakce na pevné fázi; Volatile Organic Compounds; plynová chromatografie s hmotnostně spektrometrickou detekcí; SPME; 2D gas chromatography; Humans